Effects of Cornus mas fruit hydro-methanolic extract on serum antioxidants, lipid profile, and hematologic parameters following cisplatin-induced changes in rats - Atefe Mohammadzadeh Vardin; Bita Abdollahi; Morteza Kosari-Nasab; Mehran Mesgari Abbasi (Wolters Kluwer Medknow Publications, 2017)
Cisplatin (Cis) has serious adverse side-effects that limit its clinical use. The mechanism underlying the effects is complex, including mitochondrial oxidative stress and inflammation. This study investigated whether Cornus mas, a fruit with high antioxidant contents, hydro-methanolic extract (CME) can modulate the cisplatin-induced changes. Forty Wistar rats were divided into a control group, Cis group, CME group, CME 300 + Cis group, and the CME 700 + Cis group. After the intervention, blood samples were taken for biochemical and hematological analysis. CME analysis showed noticeable total phenol and total antioxidant contents. The plasma glutathione peroxidase and catalase levels were significantly decreased and malondialdehyde and blood hemoglobin levels were significantly increased in the Cis group, which were reversed to the control levels in the CME + Cis groups. In the CME group, the red blood cell count was significantly lower and the red cell distribution width and hemoglobin distribution width levels were significantly higher. In the Cis-treated group, white blood cells, neutrophils, monocytes, basophils, and large unstained cells were significantly increased and lymphocytes were significantly decreased when compared with the control group that was reached to non-significant levels in CME 700 + Cis group. The blood cholesterol and high density lipoprotein in all CME-treated groups were significantly decreased. The eosinophils increased in the CME group significantly. The results showed considerable total antioxidant and total phenol contents and relative protective effects of CME against Cis-induced antioxidant and hematologic changes in rats.